Diseño del sistema de supresión de incendios para la planta de distribución (CIDE) de la empresa Cargill - Solano-Morales, Daniel (Instituto Tecnológico de Costa Rica, 2017)
The project deals with the design of a fire protection system for the expansion of the Cargill distribution and storage plant. The main objective is to design the fire suppression system that complies with all the guidelines dictated by the Meritorious Fire Department and the International Insurer, in order to obtain in a national way the necessary permits for the construction of the system and at the international level have I approve of the Insurer. The methodology used in the development of the project is the design based on the guidelines found in the NFPA Standards, according to the type of property to be protected and the type of conditions it presents. The main results of this project are the generation of plans for the construction and the recommendations presented in this document for future expansions where they should be taken into account at the level of maintenance of the facilities according to NFPA guidelines.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Bombas; Seguridad; Distribución; NFPA; Diseño; Research Subject Categories::TECHNOLOGY::Engineering mechanics